2020
DOI: 10.3390/jcm9030613
|View full text |Cite
|
Sign up to set email alerts
|

Chromothripsis and DNA Repair Disorders

Abstract: Chromothripsis is a mutational mechanism leading to complex and relatively clustered chromosomal rearrangements, resulting in diverse phenotypic outcomes depending on the involved genomic landscapes. It may occur both in the germ and the somatic cells, resulting in congenital and developmental disorders and cancer, respectively. Asymptomatic individuals may be carriers of chromotriptic rearrangements and experience recurrent reproductive failures when two or more chromosomes are involved. Several mechanisms ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…It is reported that TNF‐α is found in the promotion of cystitis in rat through inducing NF‐kappaB signaling pathway 30 . TP53, a tumor suppressor gene, is involved in cell cycle, senescence, and cell apoptosis via key gene regulation 31 . Since inflammation is strongly linked to canonical pathway, TP53 can inhibit inflammation in injured tissue 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that TNF‐α is found in the promotion of cystitis in rat through inducing NF‐kappaB signaling pathway 30 . TP53, a tumor suppressor gene, is involved in cell cycle, senescence, and cell apoptosis via key gene regulation 31 . Since inflammation is strongly linked to canonical pathway, TP53 can inhibit inflammation in injured tissue 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several models of the eccDNA biogenesis have been proposed: 1) The chromothripsis model ( Figure 2A ): Chromothripsis is the catastrophic shattering of a chromosome followed by massive genomic rearrangement in a random order, leading to complex genomic structural rearrangements in confined genomic regions. As the “shattering” procedure results in clustered DNA double-strand breaks (DSBs), following by DNA repairing or aberrant DNA replication, and which make it a perfect circumstance to generate eccDNA ( Nazaryan-Petersen et al, 2020 ); in 2021, Wang’s team ( Wang Y et al, 2021 ) reported that apoptosis can promote eccDNA generation in human and mouse cells. It is not surprising; apoptosis, just like chromothripsis, can induce DNA fragmentation and may provide massive DNA fragments for eccDNA formation; 2) Episome model ( Figure 2B ).…”
Section: The Biogenesis Of Eccdnamentioning
confidence: 99%
“…The first written mention of the unambiguous detection of chromothripsis was published by Nazaryan et al in 2014. The paper emphasised the necessity of implementing several complementary methods (such as FISH, karyotyping and Sanger sequencing) in order to obtain the whole picture of complex rearrangements [ 64 , 65 ]. The topic of complex cth detection reappeared in 2016, when Macera et al published a report of chromothripsis diagnostics via multiple molecular biology approaches: karyotyping, fluorescence in situ hybridisation (FISH), microarray, whole genome sequencing approach.…”
Section: Diagnostics Of Chromothripsismentioning
confidence: 99%